MOLECULAR ANALYSIS OF GENETIC STABILITY OF IN-VITRO CONSERVED POTATO MICROPLANTS - Tiwari, Jagesh Kumar (Potato Journal, 2016)
Genetic stability of 3-year-old potato microplants conserved in vitro was assessed using random amplified polymorphic DNA (RAPD), inter-simple sequence repeat (ISSR), simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) markers. A total of 38 (10 RAPDs, 11 ISSRs, 12 SSRs and 5 AFLPs) primers produced a total of 360 (42 RAPDs, 54 ISSRs, 96 SSRs and 168 AFLPs) clear, distinct and reproducible amplicons. DNA banding profiles and cluster analyses of micropropagated progeny plants were similar (100%) to their corresponding mother plants except for 70-100% by AFLP method. Cluster analysis based on the Jaccard’s coefficient classified the genotypes into four clusters (I-IV), each cluster consisting of mother plant and its derivatives. This study confirmed the genetic fidelity of potato microplants conserved for three years in vitro.